2014
DOI: 10.1186/1477-7827-12-47
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and assisted reproduction technologies: current concepts

Abstract: Accumulating evidence from animal and human studies suggests that vitamin D is involved in many functions of the human reproductive system in both genders, but no comprehensive analysis of the potential relationship between vitamin D status and Assisted Reproduction Technologies (ART) outcomes is currently available. On this basis, the purpose of this systematic review and meta-analysis was to perform an in-depth evaluation of clinical studies assessing whether vitamin D status of patients undergoing ART could… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 51 publications
5
23
0
1
Order By: Relevance
“…This overall prevalence of vitamin D deficiency was slightly lower than what has been reported for the general population of childbearing age women in the US (31 %) [3]. As Vanni et al [80] reported, a lower prevalence of vitamin D deficiency is to be expected in a population of women seeking IVF, as these women tend to have higher socioeconomic status as well as education level, both of which are factors associated with higher vitamin D levels. Garbedian et al [72] suggested that the low number of vitamin D deficient women reported in their study (1.2 %) was due to increased usage of daily prenatal vitamins.…”
Section: Vitamin D Deficiency Prevalencementioning
confidence: 55%
“…This overall prevalence of vitamin D deficiency was slightly lower than what has been reported for the general population of childbearing age women in the US (31 %) [3]. As Vanni et al [80] reported, a lower prevalence of vitamin D deficiency is to be expected in a population of women seeking IVF, as these women tend to have higher socioeconomic status as well as education level, both of which are factors associated with higher vitamin D levels. Garbedian et al [72] suggested that the low number of vitamin D deficient women reported in their study (1.2 %) was due to increased usage of daily prenatal vitamins.…”
Section: Vitamin D Deficiency Prevalencementioning
confidence: 55%
“…Since then the number of publications on this topic has grown with heterogeneous results [54]. The second study published on this association actually observed a negative effect of increasing follicular fluid vitamin D levels on IVF outcomes [55].…”
Section: Vitamin Dmentioning
confidence: 99%
“…Studies have shown that vitamin D deficiency is highly prevalent among women undergoing Controlled Ovarian Stimulation (COS) in Assisted Reproductive Technology (ART) procedures. 18 In women, vitamin D deficiency status has been associated with less IVF outcome, features of PCOS, and endometriosis. 4 Vitamin D has direct effect on Anti Mullarian Hormone (AMH) production, and thus increases longer maintenance of ovarian reserve in the patients with its higher concentration.…”
Section: Vitamin D and Female Infertilitymentioning
confidence: 99%